Socialist Ideals to Fascist Propaganda: Community Building and Secular Italian Community Welfare in Sydney 1881-1945 - Musico, Francesca A (Spunti e Ricerche, 2016)
This paper examines a history of Sydney’s secular Italian welfare associations between 1881-1945. The lack of government and church funded migrant welfare pre-empted the formation of these societies. The associations were also a response to the commitment of some popular figures to organize and bring Italians togethers for welfare provision. All these secular welfare associations were organized by political groups. Such groups were the only Italian associations who had the organizational skills and capital to finance benevolent undertakings. During the period in question, welfare was in the hands of socialists, patriots, Fascists and anti-Fascists respectively.